Infliximab inhibits bone resorption by circulating osteoclast precursor cells in patients with rheumatoid arthritis and ankylosing spondylitis. Issue 5 (24th August 2007) - Gengenbacher, M; Sebald, H-J; Villiger, P M; Hofstetter, W; Seitz, M
Abstract : Objective: To examine the effects of infliximab on bone resorption by osteoclast precursor cells (OCPs) in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS) and to compare the results with changes in disease activity. Methods: Before and during 24 weeks of infliximab treatment, peripheral blood mononuclear cells of 9 RA and 10 AS patients were seeded onto ivory wafers and adherent cells, including OCPs, were grown in medium promoting osteoclast differentiation. Bone resorption was evaluated morphometrically and correlated to disease activity. A total of 19 healthy individuals were studied in parallel. In addition, biochemical bone markers were assessed in all patients at baseline and after 24 weeks. Results: OCPs from RA patients showed a higher bone resorption at baseline when compared to AS patients. Blocking of tumour necrosis factor (TNF)α with infliximab resulted in a strong reduction of bone resorption by OCPs in both cohorts and occured faster in RA compared to AS patients. This inhibition coincided with a reduction of clinical disease activity in both patient cohorts and with an increase of serum osteocalcin levels and a relative decrease of collagen crosslinks in RA compared to AS patients. Conclusion: These results provide an explanation on the cellular level for the anticatabolic effect of TNF neutralisation on bone. The variation in the kinetics of bone resorption by the OCPs in patients with RA and AS suggests disease-specific differences in the type or in the preactivation of OCPs.